2017
DOI: 10.1097/md.0000000000005904
|View full text |Cite
|
Sign up to set email alerts
|

Mortality assessment of patients with hepatocellular carcinoma according to underlying disease and treatment modalities

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(162 citation statements)
references
References 45 publications
2
149
0
2
Order By: Relevance
“…While there has been considerable improvement in the diagnosis and treatment of HCC over the last decade, the incidence of HCC remains high, therapy response low, predisposition to developing resistance to contemporary chemo-and/or radio-therapy high, and treatment failure more common, as is evidenced by increasing incidence and mortality rates over the last 10 years, coupled with a relatively low~50% 2-year survival rate and perplexing 10% 5-year survival rate in the United States [21]; Thus, managing HCC remains a medical enigma, requiring the discovery or identification of novel actionable molecular targets and development of a more effective therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been considerable improvement in the diagnosis and treatment of HCC over the last decade, the incidence of HCC remains high, therapy response low, predisposition to developing resistance to contemporary chemo-and/or radio-therapy high, and treatment failure more common, as is evidenced by increasing incidence and mortality rates over the last 10 years, coupled with a relatively low~50% 2-year survival rate and perplexing 10% 5-year survival rate in the United States [21]; Thus, managing HCC remains a medical enigma, requiring the discovery or identification of novel actionable molecular targets and development of a more effective therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite demonstrating a significant improvement of survival over time, the median survival of 18.6 months in the later era still seems rather low. Golabi and colleagues47 looked at 2‐year survival rates of patients with HCC in the Surveillance, Epidemiology and End Results database between 2001 and 2009 and found that 75.4% of the patients had died within 2 years; further subanalysis showed mortality within 2 years for those who underwent liver transplant, hepatic resection, and nonsurgical treatment to be 29.1%, 43.7%, and 85.3%, respectively. It is likely that the high mortality rate of those patients in the nonsurgical treatment group greatly impacted the overall survival rates in their study.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In the United States, 2-year survival with HCC ranges from 30% to 44%. (1,3) Early diagnosis and treatment is essential to curbing the high mortality associated with HCC and other liver tumors. Ultrasound imaging and measuring alpha-fetoprotein (AFP) are two commonly used approaches to screen for HCC; however, there are important limitations to both of these methodologies.…”
mentioning
confidence: 99%